“Burnout,” Bioethics, and the Practice of Medicine - Koch, Tom (British Journal of Healthcare and Medical Research, 2024)
Following the recent pandemic a large number of practitioners retired or resigned from clinical service. While Covid-19 was unexceptional in its effect on health services and practitioners—we had seen similar stressors in previous epidemics/pandemics—this was unprecedented. In the past, practitioners were typically tired from caring but in the main affirmed in their vocation of caring. One reason for this change, it is argued, was the commercialized and bureaucratic view of medicine introduced with bioethics by the end of the 1970s. That cange, and its relation to practitioners, is the focus of this brief article.